Activation of σ1 and σ2 receptors by afobazole increases glial cell survival and prevents glial cell activation and nitrosative stress after ischemic stroke. Issue 3 (1st September 2016) - Katnik, Christopher; Garcia, Angela; Behensky, Adam A.; Yasny, Ilya E.; Shuster, Alex M.; Seredenin, Sergei B.; Petrov, Andrey V.; Cuevas, Javier
Abstract: Activation of sigma receptors at delayed time points has been shown to decrease injury following ischemic stroke. The mixed σ1/σ2 receptor agonist, 5‐ethoxy‐2‐[2‐(morpholino)‐ethylthio]benzimidazole (afobazole), provides superior long‐term outcomes compared to other σ ligands in the rat middle cerebral artery occlusion (MCAO) stroke model. Experiments using the MCAO model were carried out to determine the molecular mechanism involved in the beneficial effects of afobazole. Administration of afobazole (3 mg/kg) at delayed time points post‐stroke significantly increased the number of microglia and astrocytes detected in the ipsilateral hemisphere at 96 h post‐surgery. Morphological analysis of the microglia indicated that a greater number of these cells were found in the ramified resting state in MCAO animals treated with afobazole relative to MCAO vehicle controls. Similarly, fewer reactive astrocytes were detected in the injured hemisphere of afobazole‐treated animals. Both the enhanced survival and reduced activation of glial cells were abolished by co‐application of either a σ1 (BD‐1063) or a σ2 (SM‐21) receptor antagonist with afobazole. To gain further insight into the mechanisms by which afobazole lessens stroke injury, we probed the brain sections for markers of neuroinflammation (tumor necrosis factor α) and nitrosative stress ( S ‐nitrosocysteine). Data show that afobazole significantly reduces S ‐nitrosocysteine levels, but does not alter tumor necrosis factor α expression 96 h after an ischemic stroke. Taken together our data indicate that afobazole acting via both σ1 and σ2 receptors decreases stroke injury by enhancing glial cell survival, blocking ischemia‐induced glial cell activation, and decreasing nitrosative stress. Abstract : Glial cell death, activation of surviving astrocytes and microglia, and increased nitrosative stress promote expansion of the ischemic core after stroke. Using the middle cerebral artery occlusion rat stroke model, we show that afobazole activation of σ1 and σ2 receptors inhibits these events when the drug is first applied 24 h post‐stroke. Afobazole expands the therapeutic window for stroke treatment.